The perception in implementing principle 5-7 of Malaysian Sustainable Palm Oil (MSPO) among independent smallholders case of Melaka / Nurul Afiqah Mohd Zin - Mohd Zin, Nurul Afiqah (Faculty of Plantation and Agrotechnology, 2019)
The global demand for sustainable palm oil is continual increasing over the year. To supply the demand of sustainable palm oil in worldwide, the Malaysian Sustainable Palm Oil (MSPO) certification has been made mandatory by the end 2019. This study had been designed to analyse the perception in implementing principle 5-7 of Malaysian Sustainable Palm Oil (MSPO) among independent smallholders. The data was obtained from questionnaire and had been passed to 44 respondents in Sungai Rambai Melaka. The data collected has been analysed by using Statistical Package for Social Science (SPSS) to determine descriptive analysis, correlation and regression. As the result were analyzed, it showed that there is a strong positive linear relationship between perception and principle 5-7 of MSPO among smallholders. The regression analysis is 87.6% of variation in perception smallholders was explained by independent variable and another 12.4% was explained by other factors. The most principle MSPO that affects perception smallholders are principle 5 of MSPO. The main reason for the destruction of habitats and rare species caused of expansion of oil palm in developing countries is unfair allegation.